New control for Panama disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Scientists in India believe that a new control technique may prove cost-effective in controlling Panama disease the widespread fusarial wilt that inflicts serious damage on bananas. The new technique involves injecting a solution of 2% carbendazim...